Moisture content, fatty acid profile and oxidative traits of aged beef subjected to different temperature-time combinations. (November 2019) - Holman, Benjamin W.B.; Ponnampalam, Eric N.; Kilgannon, Ashleigh K.; Collins, Damian; Plozza, Tim; Hopkins, David L.
Abstract: Temperature-time combinations (TTC) effects on beef fatty acid (FA) composition, moisture content and oxidative traits were investigated. TTC were designed so temperatures were constant over each time period, and there was at most one variation in temperature within a sample's combined (total) time period. Therefore, three temperatures ( 3, 5 and 7 °C) and five time periods (6, 8, 10 and 12 d) resulted in 72 different TTC, which were compared to control samples held for 14 d at 1 °C. It was found that moisture losses increased as TTC temperature and time periods increased. There were negligible effects of TTC on FA composition. Sample TBARS and vitamin E content did not respond to TTC. A positive relationship between beef vitamin E and long chain polyunsaturated FA contents was observed. We concluded that TTC could be applied to accelerate the rate of ageing for beef and achieve comparable yield, oxidative and FA characteristics compared to conventional ageing approaches.